The Mediating Role of Job Satisfaction in the Relationship Between Human Resource Management Practices and Turnover Intention - Hanifa, Muhammad; Widagdo, Bambang; Rumijati, Aniek (Jurnal Manajemen Bisnis, 2024)
Research aims: This study examines the mediating role of job satisfaction among employees of a Power Generation Company in Indonesia and its relationship with compensation, training, career development, and turnover intention.Design/Methodology/Approach: This research utilized a cross-sectional survey involving 263 respondents representing all employees. The Partial Least Square Structural Equation Model (PLS-SEM) approach was employed to analyze the data, and SmartPLS was used to process multiple independent variables and test quantitative data.Research findings: The research findings indicate that compensation and career development do not have a significant direct effect on turnover intention. However, training and job satisfaction have a significant direct impact on turnover intention. The indirect relationship reveals that career development, through the mediating variable of job satisfaction, has no significant relationship with turnover intention. However, compensation and training, through the mediating variable of job satisfaction, have a significant relationship with turnover intention.Theoretical Contribution/Originality: The current study aims to expand on the existing literature by examining job satisfaction as a mediating variable between HRM practices (compensation, training, and career development) and employees' intention to leave (turnover intention).Practitioners/Policy Implications: Companies must provide satisfactory employee job satisfaction, as job satisfaction is a key mediating factor in the relationship between compensation and training that can influence turnover intention.Research Limitations/Implications: The practical implications of this study suggest that companies should strive to retain their employees by ensuring their well-being. The research findings indicate that providing employees with more training and certifications may increase their likelihood to seek opportunities at other companies. This outcome aligns with the human capital theory, as the knowledge, competence, and skills acquired by employees become inherent qualities associated with the employees themselves.